Synthesis and Characterization of Metal Particles Using Malic Acid-Derived Polyamides, Polyhydrazides, and Hydrazides - Muhammad Farhan Qadir; Somavia Ameen; Rida Fatima; Nadim Ullah; Gamal A. Shazly; Abu Summama Sadavi Bilal; Mehwish Nazar; Anoosha Sajjad; Tawaf Ali Shah; Yukun Yang (Molecules)
Malic acid-derived polyamides, polyhydrazides, and hydrazides exhibit strong potential for a variety of biological applications. This study demonstrates the synthesis of cobalt, silver, copper, zinc, and iron particles by a facile chemical reduction approach utilizing malic acid-derived polyamides, polyhydrazides, and hydrazides as stabilizing and reducing agents. Comprehensive characterization of the particles was performed using UV–Vis spectroscopy, FTIR, XRD, SEM, and EDX analysis. The synthesized particles included both zero-valent metals and oxides exhibiting mixed-phase compositions that may influence their functional properties. UV–vis analysis confirmed the formation of particles represented by the surface plasmon resonance (SPR) peaks specific to each metal particle. FTIR spectroscopy revealed the interaction of the metal particles with the polymer matrix owing to the significant contribution of functional groups in the processes of reduction and stabilization. Further structural insights were obtained via X-ray diffraction (XRD), which identified crystalline phases, and scanning electron microscopy (SEM), which demonstrated uniform morphologies. Additionally, energy-dispersive X-ray (EDX) analysis provided compositional details, affirming the purity and distribution of metallic elements. These findings highlight the potential of malic acid-derived polymers as versatile agents for nanoparticle synthesis with applications in catalysis, sensing, and biomedical technologies.